Modulating the nordic hamstring exercise from "zero to hero": A stepwise progression explored in a high-performance athlete - Alt, T.; Roos, T.; Nolte, K.; Modenbach, D.; Knicker, A. J.; Jaitner, T. (Journal of Athletic Training, 2023)
Background The Nordic hamstring exercise (NHE) is commonly implemented to selectively improve eccentric knee-flexor strength. However, the standard version of the exercise (leveled shanks, extended hip joint) is too strenuous for most individuals, whose muscle activity rapidly decreases at extended knee angles. Hitherto, a gradual approach to the exercise has been missing. In this exploratory case study, we investigated elite performance to introduce a stepwise progression to the NHE.